SEDIMENTS AND NUTRIENT DYNAMICS IN THE LAKE MARKERMEER, THE NETHERLANDS - Philiphi de Rozari (Universitas Gadjah Mada, 2009)
Lake Markermeer is a large fresh water lake in the centre of the Netherlands. Since Lake Markermeer is categorised as a shallow lake, it is very susceptible for sediment resuspension. The general objective of this study is to investigate sediment and nutrient dynamics in Lake Markermeer sediments. This research was carried out in a 5 months period from November 2007 until March 2008 using sediment trap methods. Sampling sites for sediment traps are located at the two fixed sites in which each sampling site had duplicates bottom and half-depth traps. The collection of the sediment traps samples was conducted every two weeks. The parameter measured in sediment traps were: sediment trap yields, Loss on ignition (LOI), total N and total P. Statistical t test analysis was utilised to compare the value of each parameter between two sampling stations as well as between bottom and half depth at the same stations.The results for the sediment trap activities showed that at the two fixed sampling stations, the sediment trap yields in the bottom part tend to be higher than half depth. This difference between bottom and half-way traps is statistically significant. Also, a significant difference was found between STA and STB, both for bottom and half-depth traps. A similar result was found for LOI. For total N and P the results showed that there were no significant differences between bottom and half-depth at the two fixed sampling stations.